Message Boards Message Boards

1
|
3264 Views
|
5 Replies
|
1 Total Likes
View groups...
Share
Share this post:

Truncated exponential distribution

Posted 3 years ago

I need to find the mean of the maximum for n independent identical random variables in a Truncated exponential distribution.

I used the following code to find it for exponential distribution:

ed = {ExponentialDistribution[\[Lambda]], n};
m = Mean[OrderDistribution[ed, 1]] ;
Print[m];

What changes should I make to make the code work on a Truncated exponential distribution on the interval [a,b]?

POSTED BY: Bilal Owaidat
5 Replies
Posted 3 years ago

You should now have enough to go on to do that yourself. If you get stuck at some point, please show what you've tried and explain where you are stuck. I would imagine you'll get more help that way.

POSTED BY: Jim Baldwin
Posted 3 years ago

You only asked for the mean. How did it "not work" for the variance? Did you get an error? Can you show what you tried?

POSTED BY: Jim Baldwin
Posted 3 years ago

Yes, you are right, I used n in the variance and it showed the original equation without making any calculations. But when I used a specific value of n, it worked perfectly. Thank you a lot.

Just one more thing if you could help me with, any idea about finding the mean and variance of the maximum for n independent non-identical random variables in a Truncated exponential distribution.

POSTED BY: Bilal Owaidat
Posted 3 years ago

Note: Edited from the original answer.

If you have specific values for $n$, then the following will work for the mean and variance of the maximum for a sample of size $n=3$:

trd = TruncatedDistribution[{a, b}, ExponentialDistribution[\[Lambda]]];
otrd = OrderDistribution[{trd, 3}, 3];
FullSimplify[Mean[otrd], Assumptions -> {b > a > 0, \[Lambda] > 0}]

$$\frac{(6 a \lambda +11) \left(-e^{3 b \lambda }\right)+18 (b \lambda +1) e^{\lambda (a+2 b)}-9 (2 b \lambda +1) e^{\lambda (2 a+b)}+e^{3 a \lambda } (6 b \lambda +2)}{6 \lambda \left(e^{a \lambda }-e^{b \lambda }\right)^3}$$

FullSimplify[Variance[otrd], Assumptions -> {b > a > 0, \[Lambda] > 0}]

$$\frac{-4 e^{3 \lambda (a+b)} (9 \lambda (a-b) (a \lambda -b \lambda +3)+155)+249 e^{2 \lambda (2 a+b)}-42 e^{\lambda (5 a+b)}-6 e^{\lambda (a+5 b)} (6 \lambda (a-b) (3 a \lambda -3 b \lambda +5)+55)+6 e^{2 \lambda (a+2 b)} (6 \lambda (a-b) (3 a \lambda -3 b \lambda +8)+115)+4 e^{6 a \lambda }+49 e^{6 b \lambda }}{36 \lambda ^2 \left(e^{a \lambda }-e^{b \lambda }\right)^6}$$

POSTED BY: Jim Baldwin
Posted 3 years ago

Thank you for your help, is this only for the mean? I tried to use it to find the variance but it didn't work.

POSTED BY: Bilal Owaidat
Reply to this discussion
Community posts can be styled and formatted using the Markdown syntax.
Reply Preview
Attachments
Remove
or Discard

Group Abstract Group Abstract